Exploration of preferences for support and coping strategies follwing suicide attempt among adolescents in Limpopo Capricorn District - Rasodi, Ngoako Matshukgane (University of Limpopo (Turfloop Campus), 2013)
The aim of the study was to explore preference for support and the different coping strategies that are employed by adolescents’ following suicide attempt in Limpopo Capricorn district. The sample comprised of 81 adolescents of both male and female who were admitted at public hospitals around the district and referred to psychology department for intervention. Using purposive sampling, data was collected through the use of a questionnaire which was divided into 1. Demographical information, 2. Multidimensional scale of perceived social support (MSPSS), 3. Ways of coping scale (WCS) which consisted of three subscales: active-cognitive, active-behavioural and avoidance strategies. Most participants reported not having support. Participants who expressed support from family, friends and significant others indicated that although family, friends and significant others were equally perceived to be an important source of support, family was more inclined to be the most preferred source of support. This preference differed according to gender as females perceived family to be the most important source followed by friends and lastly significant others, while males order of preference was friends followed by significant others and lastly family; indicating that males are more inclined to have their friends as the most preferred source of support than females. The findings of the study also indicated that suicidal adolescents used avoidance strategies followed by cognitive and lastly behavioural strategies. A significant relationship was established in the use cognitive strategies and coping by adolescents who viewed their support structures as supportive and also with active behavioural strategies. On avoidance strategies there was no significant relationship established highlighting the possibility that those adolescents who feel that they have no support use avoidance as a coping strategy. The recommendations made on the results from this study are that research in suicide should be a continuous process that keeps up with the changing family, political and cultural dynamics of our society. This is crucial since what is considered crucial support today for the adolescent, might not necessarily be viewed as relevant support for the adolescent in the
Thesis (M.A. (Clinical Psychology)) --University of Limpopo, 2013
Keywords: Adolescents; 362.28; Control (Psychology) in adolescence